Comparative study of the physicochemical, compositional and functional properties of eight flours obtained from different plant materials found in Colombia. (December 2016) - Lopera-Cardona, Seneida; Gallardo, Cecilia; Umaña-Gallego, Jairo; Gil, Lina María
The physicochemical, compositional and functional properties of flour from green plantains ( Musa acuminata ) of the large green plantain variety, oyster mushrooms ( Pleorotus ostreatus ), pineapple peel ( Ananas comosus ) of the 'apple pineapple' variety, yellow peas ( Pisum sativum ), chickpeas ( Cicer arietinum ), whole grain rice ( Oryza sativa ), whole grain corn ( Zea mays ) and whole grain white quinoa (Chenopodium quinoa ) were evaluated by using one-way analysis of variance, Pearson correlations and principal component analysis chemical composition of the eight flours, statistically differed ( p  < 0.05). Oyster mushroom and yellow pea flours had the greatest protein content (28.92 and 21.02%, respectively), whereas the pineapple peel, peas and corn stood out for their high contents of Fe and Zn. All flours exhibited emulsifying and foaming activities, while hydration and interfacial properties showed statistically significant negative correlations. There was a clear relationship between levels of protein and carbohydrates and gelation and syneresis phenomena in thermally treated flour suspensions. According to principal component analysis of functional, physicochemical and compositional properties, flours were classified into five groups of raw materials: (1) yellow peas, (2) chickpeas, rice, corn and quinoa, (3) green plantain, (4) pineapple peel and (5) oyster mushrooms. Results are promising to formulate mixes and composite flours for fortification and/or enrichment of food products by using different technological processes.